HISTORY OF THE DEVELOPMENT OF FINE ARTS AND ITS SIGNIFICANCE TODAY - Sharabaev Ulugbek Mukhamedovich (Modern American Journals, 2025)
The visual arts have played a crucial role in human civilization, evolving over the centuries to reflect changing cultural, social, and technological landscapes. The three articles cover the history of visual art production from modern civilizations to the present day. It explores the importance of visual art in modern society, and the editorial emphasizes its role in fostering creativity, cultural communication, and the expression of emotions.
Keywords: History of visual arts, society, 19th-20th centuries, traditional, impressionism and cubism, beauty, meaning, and thought.